Culturally Responsive Teaching Modules to Improve Reading Comprehension of Narrative Text for Elementary School Students: Modul Ajar Responsif Budaya untuk Meningkatkan Pemahaman Membaca Teks Narasi Siswa Sekolah Dasar - Kuswandi, Kuswandi (Pedagogia : Jurnal Pendidikan, 2025)
This study aims to develop and examine the effectiveness of a Culturally Responsive Teaching (CRT)-based module to enhance narrative text reading comprehension among grade 4 elementary students. CRT was selected for its strength in integrating the local cultural context of West Java into the learning process, creating a cognitive bridge between students' daily experiences and the material. The research employed a modified 4D R&D model that included cultural analysis. Participants involved material, language, and media experts, teachers, and 30 fourth-grade students from SDN Puncakmanis, Sukabumi Regency. Data were collected using expert validation, questionnaires, and reading comprehension tests. Results indicated that the CRT-based module was valid (material 87.27%, language 88.33%, media 85%), practical (teachers 93.33%, students 87.22%), and effective—evidenced by an N-Gain of 0.61 (medium category) and an improvement in learning completeness from 40% to 100%. The findings suggest that CRT-based learning can significantly improve students' reading skills and support the integration of cultural relevance in education. However, the study's limitation lies in its specific cultural scope (West Java), suggesting a need for adaptation in other regions with different cultural backgrounds. Additionally, implementation was limited to a single school, requiring broader application for generalization. Highlights: Culturally Relevant: Integrates West Java culture to boost reading comprehension. Well-Validated: Scored highly in expert and user evaluations. Effective Results: Improved learning completeness from 40% to 100%. Keywords: Teaching Module, Culturally Responsive Teaching, Reading Comprehension Skills, Narrative Text, Elementary School